(3GbJQGM GdbQjM hGLJQGM GdLQjMs - (3Ydj Hf YHO GdZfj GdagQj GdMUQj GdbjQhGfj , CHh GdMSf,J (B488 (3g` s
(3ChdgG (B:s
"(3GdMeO ddg eGdc Gdedc(B" s
(3BNQgG (B:s
"(3bGajI GdHGA(B" s
(3hgh OjhGf TYQ jTJed Ydi bUGFO eQJHI Ydi MQha GdeYLe hcdgG ai QKGA hdOgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B125 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B693s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B110 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B426 s
Keywords: (3GdCOHs